Two essential aminoacids obtained from the Turda 250L and Fundulea 345L corn seeds, recommended for consumption - Sorin Jianu; Daniela Laura Buruiană; Ștefania Eliza Tănasie; Alexandru Chiriac (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
This paper is a continuation of studies made in 2011 ["Maize contains tryptophan and methionine - two acids essential for human health" Olimpia Pandia, I.Saracin, Magazine Metalurgia International, nr.5, 2013], to determine the amounts of protein in corn and especially some of the essential amino acid, necessary for the human body, and the establishment of hybrids in the study with high biological value to be used more in crops. Were included in the study 2 corn hybrids Turda 250 L and Fundulea 345 L,which were analyzed existing amino acids in grains, but especially content of lysine and threonine, as well their adaptation in hilly zone where were placed experiences; there is a temperate continental climate, where absolute maximum temperatures are 40 0C, and minimum -300C and average annual precipitation about 600-700 mm/year.
Keywords: 330; amino acids; threonine; proteins; lysine; hybrids